OPEN DEFECATION AS A CHALLENGE TO PUBLIC HEALTH IN GIWA LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Abdulkadir, H.; Usman, A. K.; Abdullahi, Ahmad Hamza (FUDMA Journal of Sciences, 2023)
Open defecation is a threat to public and environmental health, it affects the occurrence and spread of mainly communicable diseases. This study examines the compliance of people to Community Led Total Sanitation (CLTS) and challenges of the program to reduce the existence of open defecation in Giwa Local Government Area (LGA). The study employed the use of questionnaire and structured interview as a source of data. Descriptive statistics and thematic framework were used for the analysis while charts and themes were used to present the findings. Results revealed that majority (56%) of the respondents were satisfied with the level of how community complied with the program. The findings also revealed that majority (31.30%) of the respondent’s considered poverty as the greatest challenge to the success of the program. Some of the key informants were also of the view that CLTS is highly applicable towards reduction in the rate of open defecation in the area. Therefore, the study recommends the provision of incentive to the people that will reduce the rate of poverty for the successful implementation of the program